Keterampilan Teknologi Informasi Terhadap Penyerapan Kerja Di Indonesia - Nasha Fahriza; Muhammad Irwan Padli Nasution (Yayasan Salam Cerdas Al-Fattah, 2025)
This study aims to comprehensively analyze the impact of information technology (IT) development on unemployment levels in Indonesia, emphasizing how digital innovation drives structural changes in the labor market. The primary objective is to determine the extent to which IT advancement contributes to two major outcomes: job displacement caused by automation and the creation of new employment opportunities driven by the digital economy. Employing a quantitative approach, this research utilizes secondary data from Statistics Indonesia (BPS), covering labor indicators and national digital development trends. The analysis reveals that IT penetration generates an ambivalent effect. Automation in manufacturing and labor-intensive industries reduces demand for traditional labor, while digital sectors such as financial technology, e-commerce, and platform-based jobs demonstrate significant growth in providing new employment opportunities. Therefore, IT development does not merely increase unemployment; instead, it triggers a transformation in work patterns that requires skill upgrading and workforce adaptability. The success of this transformation largely depends on the readiness of human resources and the government’s ability to implement adaptive policies, training programs, and sustainable digital ecosystem support.